KGB activity against lithuanian emigree in national revival period (1988–1991) - Juodis , Darius (Genocidas ir rezistencija, 2006)
Once started, the ‘perestroika’ (‘reform movement’) changed the established order in the Soviet Union. The Soviet security organs also had to adapt to the new changes. Their capacity for harsh action was severely limited, and the accompanying Lithuanian national revival brought along many unsolvable problems. This was also true of the activities of the Soviet security branch of the LSSR against the Lithuanian diaspora. With the beginning of the ‘reform’ and the national revival in Lithuania, the Soviet special services were reluctant to fundamentally change their attitude towards the Lithuanian emigrants as an irreconcilable enemy. In some respects, the chekist attitude remained unchanged until the closure of the KGB unit on the Lithuanian territory. During the years of national revival the Soviet security operations against the Lithuanian diaspora were not effective, and the work of the agents was hampered, yielding no significant results. Many insoluble problems were encountered while trying to achieve the intended targets. Moreover, many of the planned operations were no longer in the position to change the overall situation substantially because the tide turned against KGB.